KNOWLEDGE AMONG SULAIMANIYAH POPULATION TOWARDS INJECTABLE FACIAL FILLERS - Omer, Shahen Hiwa; Amin, Zanyar Mustafa; Hawramy, Falah Abdulla (Journal of Sulaimani Medical College, 2025)
Background Any operation that involves cosmetic correction and alteration of existing bodily features is referred to as a cosmetic procedure. It also covers surgical operations like liposuction, rhinoplasty, breast augmentation, and minimally invasive procedures like botulinum toxin injections and fillers. Objectives To explore and evaluate participants’ personal and subjective views on facial fillers in the Sulaimani governorate Patients and Methods One hundred and sixty-one participants were recruited over three months from 6 January 2022 to 8 April 2022; all the participants were approached with a questionnaire regarding their personal and subjective views on facial fillers, and informed consent was taken before participating. Results The recruited population for the work includes 111 females and 60 males, with an F/M ratio of 1.85. The main reason listed by most of the participants (n=102, 69.56%) who have or are considering undergoing facial fillers are their concerns about visible ageing signs and facial appearance; the (n=29, 18.01%) listed that people’s influence and the fact that they compare themselves with other people and people from the social media has encouraged them to opt facial fillers. Conclusion Half of the participants understood the procedure enough, although they needed more information regarding the facial fillers’ side effects. Most participants do not even feel they would need to hide that they have undergone any procedure, which is the ultimate level of acceptance.
Keywords: Acceptance; facial fillers; facial ageing